Fundos de investimentos de 2003 a 2015: Proxy de lucro e análise da composiç\~ao da carteira por segmento de investidor, classe de fundos e categoria de ativos - Adriana Nunes Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Investment funds are key institutions for understanding the dynamics of a country's financial wealth and for analysing the interaction between wealth owners and the macroeconomic policy management. This text has three fundamental objectives: firstly, it seeks to construct a profit proxy of the investment fund industry for the analysis of its evolution in Brazil, from 2003 to 2015. The first task is to conceptualize it, the second is its measurement under the various possible cuts, given the availability of data. Secondly, it seek to analyse how the wealth managed by the sector moved, under three distinct lenses: by class of funds, by type of assets and by segment of investor. Finally, the changes in the portfolios managed by the five largest fund managers - which in December 2015 were responsible for the management of 70% of the total net assets of the investment funds - BB-DTVM, BRAM (Bradesco Asset Manager), Caixa, Itaú and Santander are examined. The final section of the paper brings the main conclusions of the research.
Keywords: G23; 330; institutional investors; investment funds; profits